Pharmacokinetics and Tissue Residue Profiles of Enrofloxacin in Crucian Carp (Carassius auratus gibelio) Following Single and Multiple Oral Administration - Shan, Qi; Huang, Heqing; Zheng, Guangming; Yin, Yi; Zhu, Xinping; Ma, Lisha; Zhou, Hao; Xie, Wenping; Li, Lichun; Liu, Shugui; Wang, Jingxin (Frontiers in Veterinary Science, 2022)
The pharmacokinetics, tissue distribution and elimination of enrofloxacin (ENR) and its metabolite ciprofloxacin (CIP) were investigated to the crucian carp (Carassius auratus gibelio) following single (20 mg/kg b.w.) and multiple oral administration (20 mg/kg b.w. once daily for 5 days) at 28°C. The concentrations of ENR and CIP in the plasma and tested tissues (muscle/skin, liver and kidney) were detected simultaneously by HPLC, and the pharmacokinetic data were analyzed with a non-compartmental model using WinNonLin 6.1 PK software. The pharmacokinetic characteristics of ENR in crucian carp exhibited slow absorption, wide tissue distribution and long elimination half-life. In the single dose group, the peak concentrations (Cmax) of ENR in the plasma, muscle/skin, liver and kidney were 8.93 μg/mL, 13.9 μg/g, 31.2 μg/g and 27.3 μg/g, respectively, observed at 3 h, 6 h, 1 h and 3 h after dosing. The elimination half-lives (T1/2z) of ENR in plasma, muscle/skin, liver and kidney were calculated to be 67.4, 82.8, 94.4 and 114 h, respectively. In the multiple dose group, the Cmax of ENR in the plasma, muscle/skin, liver and kidney were 18.4 μg/mL, 26.8 μg/g, 82.8 μg/g and 74.5 μg/g, respectively, achieved at 3 h, 6 h, 1 h and 1 h after the last dose. The T1/2z of ENR in plasma, muscle/skin, liver and kidney were calculated to be 76.4 h, 91.5 h, 114 h, and 148 h, respectively. Significant accumulations of ENR and CIP were observed in the plasma and tissues of crucian carp during the multiple dose administration, possibly due to their long elimination half-lives. In both dose group, the AUC0-∞ for both of ENR and CIP followed the order of liver > kidney > muscle/skin > plasma. The finding suggested that liver may play an important role in the metabolism of ENR. According to the calculated PK/PD indices of Cmax/MIC and AUC24h/MIC, the multiple-dose regimen would be highly effective against pathogenic bacteria with MIC value of 1.84 μg/mL. Depletion studies indicated that a withdrawal period of at least 29 d or 32 d was necessary to guarantee food security after single or multiple oral gavage administration at 28°C.